High-Fidelity in Urgency-Emergency Simulation: validation of a tool to determine the satisfaction of participants - Calamassi, Diletta; Nannelli, Tiziana; Guazzini, Andrea; Bambi, Stefano; Gioachin, Giampaola; Pini, Riccardo; Rasero, Laura (Acta Biomedica Atenei Parmensis, 2016)
Background and aim of the work: In literature there are some tools to measure the satisfaction level related to high-fidelity simulation experience. This paper reports the construction and validation of a specific unique questionnaire in Italian (SESAF - Satisfaction of High-Fidelity Simulation Experience). Methods: After having reviewed various tools available in literature, and conducted some focus groups with high-fidelity simulation experts, the authors produced the SESAF tool. It was administered to 237 Physicians and nurses participated in high-fidelity simulation of emergency codes. Results: The factorial solution included 7 factors explaining the 71.65% of the total variance. Cronbach Alpha, reported an excellent reliability (0.97). Conclusions: SESAF can make comparable the satisfaction levels of HFS trainees among various centers.